The Effect of Motivation, Leadership and Competence on Employee Performance of Makassar City Bappeda Office. - St. Sukmawati S; Roslina Alam (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2019)
Effect of Motivation, Leadership and Competence on Employee Performance of Makassar City Bappeda Office. The purpose of this study was to determine the Effect of Motivation, Leadership and Competence on Employee Performance at the Makassar City Bappeda Office. The population in this study all employees in the Makassar City Bappeda office were 50 with ASN status, all of whom were respondents. Data collection methods in this study were questionnaire, interview, and documentation. The data analysis method uses descriptive and quantitative methods, namely multiple linear regression analysis used to measure the effect of motivation, leadership and competence on employee performance at the Makassar City Bappeda Office. The results of this study indicate that the independent variable Motivation, and Competence together have a positive and significant influence on the dependent variable (employee performance), while the leadership variable has a significant negative effect. The coefficient of determination (R2) is 0.622, the coefficient of determination states that the variables of motivation, leadership and competence can only explain or contribute to variations in changes in employee performance by 62.2 percent.